Eksistensi Androgini di Kalangan Selebgram Komunitas Penyegaran di Kota Banjarmasin - Latifah; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2025)
The growing understanding of gender in freedom of expression has given rise to the phenomenon of androgynous fashion, one of which is the celebritygram. The purpose of this research is how the existence of the celebrities of the Refreshing community in the city of Banjarmasin in self-image with the androgynic style. This research uses a qualitative approach with the phenomenological method interactively by interviewing 4 speakers where the researcher wants to describe the experience of the informants to get an overview of the androgynous celebrity on Instagram social media in the perception of the androgynous celebrity in the Refreshing community. To analyze data using data analysis from Judith Butler and Jacques Derrida. The results show that celebrities use social media, especially Instagram, as a space to express their androgynous existence, they confidently display a combination of masculine and feminine styles, through the selection of clothing, accessories, and other physical looks, the content they share reflects their androgynous identity and aims to build a unique and attention-grabbing self-image. Support androgynic self-expression by creating online safe spaces, encouraging collaboration, and holding positive campaigns. Strengthening the Refreshing community through community activities, support networks, and mentorship programs. Improve research and understanding by conducting further research, using gender analysis, and conducting interdisciplinary dialogue. Increase awareness and education by increasing public awareness, promoting tolerance, and fighting discrimination. By applying these suggestions, it is expected to support androgynic self-expression, strengthen the Refreshing community, improve research and understanding of androgyny, and increase public awareness and education about gender and gender identity.